Intermittent enteral nutrition may increase gastrointestinal complications and mortality in critically ill patients - Hu, Panxin; Wu, Haopeng; Zhang, Kai; Li, Anan; Chen, Qiu (Frontiers in Nutrition, 2025)
BackgroundEnteral nutrition (EN) is a cornerstone of nutritional support in critically ill patients. The optimal EN delivery strategy for critically ill patients remains controversial, with conflicting evidence regarding potential impacts on complications and clinical outcomes.ObjectivesThis meta-analysis aimed to compare the effects of intermittent enteral nutrition (IEN) versus continuous enteral nutrition (CEN) in critically ill patients.MethodsA comprehensive search of PubMed, Embase, Scopus, and the Cochrane Library was performed from inception to June 25, 2025. Randomized controlled trials (RCTs) comparing IEN and CEN in critically ill patients were included. Primary outcomes included gastrointestinal complications (diarrhea, abdominal distension, vomiting, constipation, gastric retention, and aspiration pneumonia), intensive care unit (ICU) mortality rate, length of ICU stay, and achievement of nutritional goal. Pooled relative risks (RRs) and mean differences (MDs) with 95% confidence intervals (CIs) were calculated using random-effects models.ResultsFifteen studies involving 1,406 patients were analyzed in this meta-analysis. In the overall critically ill population, IEN was associated with an increased incidence of diarrhea (RR 1.52, 95%CI 1.10 to 2.10, I2 = 16%) and abdominal distension (RR 2.38, 95%CI 1.17 to 4.83, I2 = 0%), higher ICU mortality (RR 1.39, 95%CI 1.02 to 1.89, I2 = 0%), and prolonged length of ICU stay (MD 0.81, 95%CI 0.18 to 1.45, I2 = 0%). Subgroup analysis further confirmed these findings in mechanically ventilated patients. In contrast, no significant differences in outcomes were observed between the two nutrition strategies in non-mechanically ventilated patients.ConclusionThis meta-analysis demonstrates that CEN appears superior to IEN among critically ill patients, particularly in those requiring mechanical ventilation. These results support for the preferential use of CEN in mechanically ventilated critically ill patients, while emphasizing the need for individualized nutritional management strategies that account for patient-specific factors and gastrointestinal tolerance.Systematic review registrationThe study protocol was prospectively registered with the Open Science Framework (https://osf.io/krs8v).